Advanced environmental exercise physiology - Cheung, Stephen S. 1968; Ainslie, Philip N. 1974 (Human Kinetics, Inc., 2022)
"Short, factual description of the book (summary of what it includes, without subjective or promotional language.) This book, for upper undergraduate and graduate students and professionals in the field, is used to provide an overview of how the environment impacts exercise"